Coralligenous banks along the western and northern continental shelf of Sardinia Island (Mediterranean Sea). Issue 2 (1st December 2022) - De Falco, Giovanni; Conforti, Alessandro; Brambilla, Walter; Budillon, Francesca; Ceccherelli, Giulia; De Luca, Mario; Di Martino, Gabriella; Guala, Ivan; Innangi, Sara; Pascucci, Vincenzo; Piazzi, Luigi; Pireddu, Laura; et al.
ABSTRACT: Mapping of coralligenous banks was carried out along the continental shelf of the northern and western margin of Sardinia Island (Italy, western Mediterranean Sea) in the context of the European Marine Strategy Framework Directive (MSFD, 2008/56/EC). Coralligenous banks are bioconstructions produced by calcareous coralline algae. Seafloor mapping was carried out through multibeam echosounder surveys and video transects, using a Remote Operating Vehicles (ROV), in areas not formerly explored. A high-resolution digital model of the seabed (DTM) was obtained from multibeam data. A total surface of 436 km2 of sparse patches of coralligenous banks was mapped in the depth range 40-160 m. A final map of coralligenous habitat distributions along the western and northern continental shelf of Sardinia (scale 1:250, 000) was produced. The base-map is formed by the shaded DTM of the seabed. Other mapped features include the edge of the continental shelf and the distribution of rocky seabed.